Stereoselective Syntheses of α,β-Unsaturated γ-Amino Esters Through Phosphine-Catalyzed γ-Umpolung Additions of Sulfonamides to γ-Substituted Allenoates - Zhou, Qing-Fa (Tetrahedron Lett, 2015)
α,β-Unsaturated γ-amino esters can be synthesized efficiently and stereoselectively through phosphine-catalyzed γ-umpolung additions of sulfonamides to γ-substituted allenoates. The structures of the sulfonamide and γ-substituted allenoate partners can be varied to achieve a range of α,β-unsaturated γ-amino esters with potentially interesting chemical and biological properties.